Quality and Grain Yield Attributes of Rwandan Rice (Oryza sativa L.) Cultivars Grown in a Biotron Applying Two NPK Levels - Alphonsine Mukamuhirwa; Helena Persson Hovmalm; Rodomiro Ortiz; Obedi Nyamangyoku; Eva Johansson (Journal of Food Quality)
High-yielding rice cultivars with good processing quality and rich in nutrition suitable to a changing climate are of particular importance for future rice-based food production. Here, seven Rwandan rice cultivars were grown in a climate chamber of the biotron facility at the Swedish University of Agricultural Sciences, to be evaluated for their grain yield, nutritional composition, and dough mixing properties. Two different levels of inorganic fertilizer were applied weekly from the seedling stage until flowering. Significant differences for grain yield and quality attributes were found between cultivars. Jyambere showed significantly the highest yield while Ingwizabukungu, Nemeyubutaka, and Jyambere were high in mineral elements content. Ndamirabahinzi and Mpembuke had the highest levels of TPC and TAC. Generally, the lower fertilizer dose resulted in a better performance of the cultivars for both yield and quality attributes. Significantly higher content of Fe, Ca, and Ba was found in grains from the moderate fertilizer dose, whereas K, Na, P, S, Zn, Cd, and Pb increased in grains from the higher fertilizer dose. The cultivar Ndamirabahinzi showed less variability of evaluated characters across fertilizer doses. The results from this study may be used for rice breeding of cultivars with high yield and good grain quality.